Surfactant‐modified parathyroid hormone fragments with high potency and prolonged action: Structure‐informed design using glycolipid surfactant conjugation. Issue 5 (15th March 2021) - Nestor, John J.; Wang, Wei
Abstract: The pharmaceutical properties of peptides (high potency and specificity with low toxicity) make them an attractive therapeutic class but typically short duration of action and low bioavailability can limit their usefulness. Here, we begin evaluation of a new class of peptide modification, glycolipid surfactant conjugation, designed to extend the half‐life of peptide therapeutics. This work illustrates ease of synthesis and conjugation, range of modulation of pharmacokinetic/pharmacodynamic behavior and acceptability in vivo of this approach. Proof of concept used parathyroid hormone and showed that an N‐terminal fragment can be modified, informed by the parathyroid hormone receptor x‐ray structure, to produce high potency, enhanced intrinsic efficacy and prolonged action in vivo . This suggests daily (hypoparathyroidism) or weekly (osteoporosis) administration with biological sequelae (stem cell maturation to osteoblasts) throughout the week. Compound 7 was chosen for advanced study. Exploration of the physical properties and development potential of glycolipid surfactant‐modified peptides are underway with additional peptide therapeutics. Abstract :